1936
DOI: 10.1084/jem.64.2.253
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Outlying Bone Marrow Accompanying a Local Increase of Temperature Within Physiological Limits

Abstract: A great difference exists in the adult bone marrow of central bones as compared with outlying bones of the mammalia and avia, the distal bones being at a great disadvantage from the standpoint of blood cell production. Several experimental procedures are reported by which this disadvantage is overcome and in consequence fatty marrow of outlying bones is replaced by red marrow occurring chiefly at the epiphyseal regions, unless a low oxygen stimulus is also provided when marrow of the diaphysis becomes involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0
2

Year Published

1942
1942
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(30 citation statements)
references
References 13 publications
4
24
0
2
Order By: Relevance
“…This is in agreement with conclusions reached in studies of the distribution and behaviour of the fatty marrow (6, 7). The present findings also appear to be consistent with those of H uggins and co-workers (8,10), which suggested a relationship between the degree of marrow activity and the level of marrow temperature. In this connection, it is noteworthy that the same authors (9) concluded that in the rat and rabbit, the temperature of the more central sites of the marrow was similar to that in the peritoneal cavity but there was a decrement in marrow temperature as one passed down the limbs and (in the rat) the tail; the measure ments of marrow temperature made by G igante and T orlontano (3) in the rabbit also support this conclusion.…”
Section: Resultssupporting
confidence: 93%
“…This is in agreement with conclusions reached in studies of the distribution and behaviour of the fatty marrow (6, 7). The present findings also appear to be consistent with those of H uggins and co-workers (8,10), which suggested a relationship between the degree of marrow activity and the level of marrow temperature. In this connection, it is noteworthy that the same authors (9) concluded that in the rat and rabbit, the temperature of the more central sites of the marrow was similar to that in the peritoneal cavity but there was a decrement in marrow temperature as one passed down the limbs and (in the rat) the tail; the measure ments of marrow temperature made by G igante and T orlontano (3) in the rabbit also support this conclusion.…”
Section: Resultssupporting
confidence: 93%
“…Farber, unpublished). Consistent with human findings, in 1889 Ranvier recorded the presence of a MAT gradient in the vertebrae of rats ranging from predominantly cellular, red marrow in the lumbar vertebrae to fatty, yellow marrow in the tail (Huggins & Blocksom, 1936; Ranvier, 1889). This historical finding has since been reobserved in mice and used as the basis for studies of MAT regulation of bone formation and hematopoiesis (Naveiras et al, 2009; Wronski, Smith, & Jee, 1981).…”
Section: Introductionsupporting
confidence: 56%
“…Marrow composition is highly affected from variations in temperature. Huggins et al [33][34][35] evidenced that the fat content of bone marrow in the limb bones (femur, radius) are higher than the bones in the central parts of the body (ribs, vertebra). This was suggested to be associated with greater body temperatures in central bones.…”
Section: Rheologymentioning
confidence: 99%